Combat Stress in Pre-modern Europe
IX, 204 p. 1 illus.
Keywords: This book examines the lasting impact of war on individuals and their communities in pre-modern Europe. Research on combat stress in the modern era regularly draws upon the past for inspiration and validation, but to date no single volume has effectively scrutinised the universal nature of combat stress and its associated modern diagnoses. Highlighting the methodological obstacles of using modern medical and psychological models to understand pre-modern experiences, this book challenges existing studies and presents innovative new directions for future research. With cutting-edge contributions from experts in history, classics and medical humanities, the collection has a broad chronological focus, covering periods from Archaic Greece (c. sixth and early fifth century BCE) to the British Civil Wars (seventeenth century CE). Topics range from the methodological, such as the dangers of retrospective diagnosis and the applicability of Moral Injury to the past, to the conventionally historical, examining how combat stress and post-traumatic stress disorder may or may not have manifested in different time periods. With chapters focusing on combatants, women, children and the collective trauma of their communities, this collection will be of great interest to those researching the history of mental health in the pre-modern period. Owen Rees is Associate Lecturer in Ancient History at Manchester Metropolitan University in the UK. An ancient Greek historian with a recognized expertise in the historiographical debate surrounding ancient post-traumatic stress disorder, he has published widely on ancient Greek socio-military history and the medical humanities. Kathryn Hurlock is Reader in Medieval History at Manchester Metropolitan University in the UK. She is co-ordinator of the Returning Soldier Network, a collaborative network examining the figure of the returning soldier or veteran from the ancient world to the modern day. Kathryn has published widely on the crusades, including two monographs on aspects of British crusading. Jason Crowley is Senior Lecturer in Ancient History at Manchester Metropolitan University in the UK, where he specializes in the psychology of combat and combat motivations. As a comparative historian, he works with theories and evidence generated by the experience of modern warfare, but his main focus is on the citizens of Classical Athens who served as hoplites, heavy-infantrymen, during the wars of the fifth and fourth centuries BC.